Editorial (diségno, 2021)
An introductionIssue No. 8 of diségno represents an ‘exception,’ or rather a ‘variant’ of the program of events of the Unione Italiana per il Disegno; a necessary variant, in adaptation to the pandemic wave that has changed the life of the entire world for over a year.The 42nd International UID Conference entitled Connettere. Un disegno per annodare e tessere / Connecting. Drawing for weaving relationships, which should have been held in mid-September 2020 on the Calabrian shores of the Messina Strait area, was postponed to the following year, same period. In substitution it was decided to organize a Study Day on the discipline in reference to the current hardships that the pandemic has imposed on us.The Covid-19 pandemic will, therefore, leave a trace even in the life calendar of the UID, and on the uninterrupted sequence of the forty-one annual conferences that to this day have characterized the association’s scientific structure... [read more]